Enhancing Students’ Spatial Reasoning and Applied Geometry Problem-Solving through GeoGebra-Assisted Project-Based Learning - Sondang Noverica; Arisan Candra Nainggolan (Sean Institute, 2026)
This study investigated the effectiveness of GeoGebra-assisted Project-Based Learning in improving students’ spatial reasoning and applied geometry problem-solving ability in an Applied Geometry course. The study employed a quantitative approach with a quasi-experimental pretest-posttest design involving 30 students. The intervention integrated dynamic geometry visualization through GeoGebra with project-based learning activities that required students to construct, analyze, revise, and present applied geometry models. Data were collected using spatial reasoning and applied geometry problem-solving tests administered before and after the intervention. The results showed that students’ spatial reasoning increased from a pretest mean score of 61.27 to a posttest mean score of 82.43, while their applied geometry problem-solving ability increased from 58.80 to 80.67. The normality test indicated that all data were normally distributed, and the paired-sample t-test showed significant improvements in both variables with p < 0.001. The normalized gain scores were 0.55 for spatial reasoning and 0.53 for applied geometry problem-solving, both categorized as moderate. These findings indicate that GeoGebra-assisted Project-Based Learning is an effective instructional approach for strengthening students’ visual-spatial understanding and contextual geometry problem-solving ability.